Fatores associados à hipovitaminose D em crianças e adolescentes participantes de um projeto social - Oliosa, Polyana Romano (2022)
Quantitative, descriptive and analytical, cross-sectional study, developed by collecting and analyzing biochemical, anthropometric, sociodemographic and lifestyle data in children and adolescents aged between 6 and 19 years old, enrolled in the institution called "Knowledge Station", located in the neighborhood Cidade Continental, Serra, Espírito Santo. The recommendations of serum vitamin D parameters are based on bone health indicators, including the presence of rickets and osteomalacia, bone mineral density and calcium absorption, however, vitamin D has an important metabolic role in the body and in children and adolescents, studies show that hypovitaminosis D is related to obesity and metabolic disorders in addition to being associated with cardiometabolic factors and dyslipidemia. In the Brazilian population, data are still incipient, therefore, the present study aims to describe the prevalence of hypovitaminosis D in the population studied, healthy schoolchildren, in addition to describing the factors associated with hypovitaminosis D and the need to carry out prevention and control measures. The results of the thesis were presented in 3 scientific articles. The first article entitled “Association of sun exposure and seasonality with vitamin D levels in Brazilian children and adolescents” resulted in participants who performed outdoor activities, as well as those who had data collected during the summer and spring, had higher levels of vitamin D. According to Poisson regression, the proportion of participants with inadequate levels of vitamin D was higher in participants evaluated during spring (PR 1.15, 95% CI 1.03 - 1.29) and winter (PR 1, 18, 95% CI 1.05 - 1.32). In addition, a higher proportion of inadequate vitamin D was observed for those involved in indoor activities (PR 1.08, 95% CI 1.01- 1.15). The second article entitled “Mediation of the effect of vitamin D on the modulation of the HOMA-IR index in children and adolescents”, we identified that the insulin concentration was significantly higher among girls classified as having a deficient concentration of vitamin D, compared to those who presented sufficient concentration (p=0.005). Boys who practiced outdoor activities had 10 higher vitamin D. For girls, insulin (12.5 mcIU/mL ± 6, vs 10.1 mcIU/mL ± 6.9; p= 0.022) and glucose (91.6 mg/ dL ± 7.0 vs 89.2 mg/dL ± 6.7; p= 0.022) was lower in practitioners of outdoor physical activity. In the Path analysis, there was no association between physical activity and HOMA-IR. Vitamin D was associated with HOMA-IR (p=0.015). The third article was a description of the study methodology, called “Study protocol for the detection of vitamin D deficiency in a healthy population of Brazilian children and adolescents”, which demonstrates how the sample calculation was performed, as well as the methodology for data collection. for the main factors that affect the concentration of vitamin D such as sex, age, race-color and percentage of fat and contact with the sun, which should be taken into account when analyzing vitamin D in children and adolescents. There is an urgent need for systematic studies on the prevalence of hypovitaminosis D in the Brazilian and Latin American population, so that we can identify the real situation of children and adolescents facing this deficiency.